Maintenance of waqf properties in Malaysia: a systematised review - Bello, Hafis; Ayob, Mohd Fairullazi; Ahmad Sarkawi, Azila (Kulliyyah of Architecture and Environmental Design (KAED) International Islamic University Malaysia, 2021)
Earlier studies have established a link between property maintenance and the lifespan of a property. The need for adequate maintenance is even more important in the case of Waqf properties due to the uniqueness of Waqf properties concerning the three core features, which are the expected social benefits, ethical use and perpetuity. Many studies have been done on this subject matter, but the one drawback is that they were not usually Waqf-specific. This paper performed a systematised literature review of studies based on maintaining properties of Waqf. The searches for the database, title and abstract screen, full-text analysis and data extraction carried out were targeted on articles that discussed maintenance of Waqf properties or indicated any form of a management model for these properties. The articles reviewed were searched from SpringerLink, Google Scholar, Emerald, SAGE, ISRA publications, as well as other databases. Of the 919 papers listed, only 12 met the requirements for inclusion. The findings indicated that while many previous studies focused on the administration and management of Waqf, Waqf institution, and the development and financing of Waqf, very few studies examined the maintenance of Waqf properties. Effective maintenance of Waqf properties is essential for the continued sustenance of the institution of Waqf and equitable distribution of income and provision of essential services to the larger society. However, the literature on the maintenance of Waqf properties is still quite scarce and of little practical guidance to managers of Waqf Properties.